Analisis Kebutuhan Modul Ajar Teks Tanggapan bermuatan Kemampuan Berpikir Tingkat Tinggi berbasis Website - Priyantoko Priyantoko; Cahyo Hasanudin; Sutrimah Sutrimah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the need for a website-based high-level thinking ability response text teaching module. This study is a type of qualitative research that focuses on the analysis of the need for a website-based high-level thinking ability response text teaching module at the junior high school level. The study was conducted at SMP Negeri 1 Kanor and MTs Muhammadiyah 1 Banjaranyar in January 2025 with 48 seventh grade students as research subjects. The results of the study indicate that the need for a website-based high-level thinking ability response text teaching module is very much needed by respondents or students. The findings of the integration are considered capable of providing an innovative and substantive learning experience.